2015
DOI: 10.1155/2015/678056
|View full text |Cite
|
Sign up to set email alerts
|

Size Effects in Residual Stress Formation during Quenching of Cylinders Made of Hot-Work Tool Steel

Abstract: The present work investigates the residual stress formation and the evolution of phase fractions during the quenching process of cylindrical specimens of different sizes. The cylinders are made of hot-work tool steel grade X36CrMoV5-1. A phase transformation kinetic model in combination with a thermomechanical model is used to describe the quenching process. Two phase transformations are considered for developing a modelling scheme: the austenite-to-martensite transformation and the austeniteto-bainite transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…To perform an accurate thermomechanical heat treatment simulation, it is necessary to have knowledge of temperature-and phase-dependent material properties. Those as well as the used numerical model are based on the study of Schemmel et al [12]. Schemmel et al calculated the residual stress formation and the evolutions of phase fractions during the quenching process in dependence of the samples sizes on the same steel grade.…”
Section: Numerical Simulationmentioning
confidence: 99%
“…To perform an accurate thermomechanical heat treatment simulation, it is necessary to have knowledge of temperature-and phase-dependent material properties. Those as well as the used numerical model are based on the study of Schemmel et al [12]. Schemmel et al calculated the residual stress formation and the evolutions of phase fractions during the quenching process in dependence of the samples sizes on the same steel grade.…”
Section: Numerical Simulationmentioning
confidence: 99%
“…These materials were used individually and combined, depending on the characteristics of the core material to be encapsulated and the specific objectives of microencapsulation. Encapsulant materials are commonly known for their flexibility, film-forming properties, lack of taste and odor, and resistance to moisture absorption [19]. Kausadikar et al (2015) microencapsulated lemon oil by spray drying to inspect its application on flour tea.…”
Section: Introductionmentioning
confidence: 99%
“…Kausadikar et al (2015) microencapsulated lemon oil by spray drying to inspect its application on flour tea. Wall materials like maltodextrin, gum arabic, modified starches and its blends were used for drying process [19] [20]. Results suggested that maximum encapsulation efficiency was observed with wall material concentration (30%), core material concentration (10%) and the inlet temperature (175°C).…”
Section: Introductionmentioning
confidence: 99%
“…For conventional hardening, Prime investigated and predicted residual stresses in a steel ring [7] and Eck and coworkers [8] modelled the residual stress evolution in a more complex component, that is, tire protection chains. Schemmel et al, in 2015, pointed out the effect of component sizes on residual stress formation [9].…”
Section: Introductionmentioning
confidence: 99%
“…When phase transformation is involved, as in ferritic steel products, the concomitant volume expansion and transformation-induced plasticity (TRIP) [10] can have a strong impact on the resulting residual stress distributions, as discussed in the work of [9]. Deng pointed out the impact of phase transformation in medium carbon steels has on residual stresses [11].…”
Section: Introductionmentioning
confidence: 99%